Mechanical, thermal and chemical resistance of epoxidized natural rubber toughened polylactic acid blends - Mat Uzir Wahit,; Azman Hassan,; Akos Noel Ibrahim,; Nurhayati Ahmad Zawawi,; Kayathre Kunasegeran, (Universiti Kebangsaan Malaysia, 2015)
Polylactic acid (PLA)/Epoxidized natural rubber (ENR-50) blends were prepared by melt extrusion followed by injection molding to fabricate the test samples. The effect of ENR-50 loadings on the morphological, mechanical, chemical resistance and water absorption properties of the blends were studied using standard methods. The toughness of the blend improved with ENR loading up to 20 wt. % but flexural and tensile strength decreased. The balanced mechanical properties were obtained at 20 wt. % ENR-50 loading. SEM showed good distribution and increased ENR particle size as ENR content increased from 10 to 30 wt. %. The differential scanning calorimeter (DSC) showed a steady drop in crystallization temperature (Tc) as ENR content increases while the glass transition temperature (Tg) remained unchanged. Water absorption was observed to increase with ENR loadings. Increase in ENR content was also observed to reduce the chemical resistance of the blends.